Phenomenological model of binary-series viscosity for analysing rheological properties of a paraffin using validated experiments. (July 2017) - Ni, Long; Qv, Dehu; Wang, Jijin; Shang, Runxin; Yao, Yang
Highlights: A new phenomenological model of binary-series viscosity was proposed. New model provided an effective definition of the rheological properties of the paraffin in the non-power-law phase. The paraffin-specific pressure drop in a horizontal pipe is approximately 1.4–6.0 times that of water at the same temperatures. Paraffin utilized in environmental control systems for thermal energy storage and transfer was viable. Graphical Abstract: Abstract: This paper presents a theoretical and experimental study on the rheological behaviours of a grade of paraffin that is intended for use in environmental control systems for the purpose of thermal storage. This research concentrates on the paraffin flow properties in a laminar flow. In the experiments, when the paraffin temperature is greater than 291.15 K, the rheological behaviours of the paraffin obey the power-law principles. However, as the paraffin temperature reduces to 291.15 K or lower, the behaviour index tends to decrease with the shear rate, and thus, the rheological behaviours of the paraffin cannot be defined by the power-law model effectively. In the non-power-law phase, the solid properties of the material become increasingly apparent as the temperature gradually reduces. Simultaneously, the paraffin fluidity decreases. Therefore, a new phenomenological model of binary-series viscosity is proposed. The binary model provides an effective definition of the rheological properties of the paraffin in the non-power-law phase (the corresponding material temperatures range from 291.15 K to 288.15 K). In general, the paraffin-specific pressure drop in a horizontal pipe is approximately 1.4–6.0 times that of water at the same temperatures.